2011
DOI: 10.1002/pd.2863
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of prenatal detection of neural tube defects in the pregnant population of the city of Barcelona from 1992 to 2006

Abstract: A high DR (94%) for isolated NTD was observed in the city of Barcelona. The single significant change across the study period was an increase in the first trimester DR for anencephaly (from 16% to 71%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
1
12
2
Order By: Relevance
“…In our cohort, anencephaly was mostly detected in the first trimester of pregnancy (69.6%) which was similar to the rate of 60% reported by Salvador et al [19] between 1997 and 2006. Our results confirmed that spina bifida remained to be predominantly diagnosed during the second trimester (81.0 vs. 72.7% for Salvador et al [19]). These authors found an 83.3% rate of first-trimester diagnosis of cephalocele whereas it was only of 42.3% in our study.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In our cohort, anencephaly was mostly detected in the first trimester of pregnancy (69.6%) which was similar to the rate of 60% reported by Salvador et al [19] between 1997 and 2006. Our results confirmed that spina bifida remained to be predominantly diagnosed during the second trimester (81.0 vs. 72.7% for Salvador et al [19]). These authors found an 83.3% rate of first-trimester diagnosis of cephalocele whereas it was only of 42.3% in our study.…”
Section: Discussionsupporting
confidence: 75%
“…Our study showed a total NTD prevalence of 14/10,000 [13,14,15,16], intermediate between the higher prevalence reported in North England (17.9/10,000) by Rankin et al [18] in 2000 and the lower prevalence reported in Spain (9.5/10,000) by Salvador et al [19] in 2011. The distribution of each NTD malformation was similar to that reported in the two above-cited papers: 41% of anencephaly (versus 43 and 46%, respectively), 13% of cephalocele (versus 6.5 and 10%) and 46% of spina bifida (versus 51 and 44%).…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Many factors may play a role in the development of defects, such as viral infections, salicylate treatment in the early period of pregnancy, radiation, hypervitaminosis, and hypoxia. Ultrasonography and computerized brain tomography (CBT) for diagnosis and magnetic resonance imaging for the assessment of sac content are utilized [5,6] . Treatment is surgical and it requires many years of follow-up.…”
Section: Introductionmentioning
confidence: 99%